Cozrta(x) sputtering target with improved magnetic properties

Heat treating CoZrTa(X) alloy targets in magnetron cathode sputtering addresses issues of magnetic flux penetration and uniformity, resulting in enhanced target efficiency and film uniformity.

JP2025061172APending Publication Date: 2025-04-10MATERION ADVANCED MATERIALS GERMANY GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025003617
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-20
Filing Date
2025-01-09
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

In magnetron cathode sputtering using ferromagnetic targets like CoZrTa(X) alloys, there are challenges with magnetic flux penetration and uniformity, leading to inefficient target utilization and non-uniform film deposition.

Method used

Heat treatment of CoZrTa(X) alloys at high temperatures reduces their magnetic permeability and flux fluctuations, resulting in improved magnetic field penetration and uniformity, thereby enhancing target efficiency and film uniformity.

Benefits of technology

The heat-treated CoZrTa(X) alloy targets exhibit reduced magnetic permeability and flux variations, allowing for increased magnetic flux penetration, improved target utilization, and more uniform film deposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061172000001_ABST
    Figure 2025061172000001_ABST
Patent Text Reader

Abstract

To provide a sputtering target based on a CoZrTa (X) alloy which can improve magnetic field penetration through a target material when used in combination with a magnetron cathode, and / or has improved magnetic uniformity, i.e., reduced variation in leakage flux density at different points of the target.SOLUTION: Provided is sputtering target consisting of alloys consisting of Co, Zr, Ta, and optionally Mo, Pd, Ni, Ti, V, W, and one or more further elements X from the group of B, which is characterized by a maximum magnetic permeability μmax of 60 or less and / or by a maximum leakage flux density (PTF) variation (FMax-FMin) / FAverage of 0.2 or less, preferably 0.15 or less, most preferably 0.10 or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a target for sputtering with a magnetron cathode, said target being based on a Co alloy containing Zr, Ta and optionally an additive comprising at least one of the elements Pt, Pd, Ni, Ti, V, W and B. [Background technology]

[0002] In the process of magnetron cathode sputtering, permanent magnets are installed behind the target (cathode) to optimize the sputtering process. These magnets are positioned in such a way that a magnetic field is created in front of the target, i.e. in the discharge space. This magnetic field has the effect of localizing the discharge plasma. Areas of the target surface where the plasma is localized undergo more vigorous sputtering, resulting in the formation of erosion grooves (or racetracks) there.

[0003] For ferromagnetic targets such as CoZrTa(X) alloys, there are two main problems that arise in this situation.

[0004] First, the magnetic flux of the permanent magnet is concentrated within the target, so only a small amount can penetrate into the discharge volume, so this problem requires the use of a very thin ferromagnetic target, or a very powerful set of magnets.

[0005] Secondly, the local reduction in the cross section of the target (erosion groove), which occurs when performing cathode sputtering with ferromagnetic targets, has the effect of increasing the magnetic flux directly above the erosion groove. As a result, the ionization of the sputtering gas increases locally and the sputtering rate also increases locally. Thus, as sputtering progresses the erosion groove becomes narrower and narrower, which is associated with a very low utilization of the target material.

[0006] Furthermore, the variation in the magnetic pass through flux measured at different points on the target should be as low as possible so that the utilization of the target material is as homogeneous as possible and the thickness of the deposited film is as uniform as possible.

[0007] Complex target designs can achieve improved magnetic field shapes and higher magnetic field penetration. By creating slots in the target perpendicular to the magnetic field direction, the magnetic resistance in the target is increased, resulting in a larger magnetic field in the discharge space (K. Nakamura et al: IEEE Transactions on Magnetics, Vol. MAG-18, pp. 1,080-1,082, 1982).

[0008] Kukla et al. (IEEE Transactions on Magnetics, Vol. MAG-23, pp. 137-139, 1987) describe a cathode for ferromagnetic materials consisting of several individual targets arranged in two planes, one above the other, to obtain a stronger magnetic field. However, these designs are more expensive and make magnetron cathode sputtering more difficult to operate.

[0009] EP 535314 A1 relates to a platinum-cobalt alloy sputtering target consisting essentially of 10-55 wt. % platinum; 1-15 wt. % of a first additive element selected from the group consisting of nickel and tantalum; 1.5 wt. % or less of a second additive element selected from the group consisting of boron, titanium, lanthanum, cerium, neodymium, beryllium, calcium, zirconium and silicon; 20 wt. % or less of chromium; and the balance cobalt. The magnetic permeability of the target is 30 or less. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] European Patent Application Publication No. 535314 [Non-patent literature]

[0011] [Non-Patent Document 1] K. Nakamura et al., IEEE Transactions on Magnetics, Vol. MAG-18, pp. 1,080-1,082, 1982 [Non-Patent Document 2] Kukla et al., IEEE Transactions on Magnetics, Vol. MAG-23, pp. 137-139, 1987 Summary of the Invention [Problem to be solved by the invention]

[0012] It is an object of the present invention to provide target materials based on CoZrTa(X) alloys which, when used in magnetron cathode sputtering, have improved magnetic properties, i.e., which, when used in conjunction with a magnetron cathode, allow for improved magnetic field penetration through the target material, and / or which have improved magnetic homogeneity, i.e., reduced variation in leakage flux density at different points of the target. [Means for solving the problem]

[0013] The present invention is based on the discovery that such a sputtering target can be provided by heat treating CoZrTa(X) alloys at high temperatures to reduce the magnetic permeability of the alloy and also reduce the magnetic flux fluctuations. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention therefore relates to a sputtering target consisting of an alloy consisting of Co, Zr, Ta and optionally one or more further elements X from the group Mo, Pd, Ni, Ti, V, W and B, in which the maximum magnetic permeability μ max is 60 or less, and / or the maximum leakage flux density (PTF) variation of the target (FMax -F Min ) / F Average is less than or equal to 0.2, preferably less than or equal to 0.15, and most preferably less than or equal to 0.10, F Max is the maximum magnetic flux density measured at the measurement point on the target, F Min is the minimum magnetic flux density measured at the measurement point on the target F Average is the average magnetic flux density, i.e. the sum of the magnetic flux densities measured at all measurement points divided by the number of measurement points, Measurements are performed at seven different equally spaced measurement points on the target, as described below.

[0015] The sputtering target of the present invention has a low magnetic permeability, which allows for an increased magnetic flux through the target and reduces the variation of magnetic flux at different points on the target, thereby avoiding or at least reducing the major problems mentioned above in magnetron sputtering and achieving the objectives of the present invention.

[0016] The targets of the present invention can be manufactured with increased thicknesses that provide the user with longer target life, better film uniformity, and a more consistent sputtering rate over the life of the target.

[0017] Preferably, the total amount (at.%) of element X is less than the greater of the two additives (at.%) of Ta or Zr, Zr is preferably present in the alloy in an amount of 2 to 8 at.%, more preferably 3 to 7 at.%.

[0018] Ta is preferably present in the alloy in an amount of 2 to 8 at.%, more preferably 3 to 7 at.%.

[0019] If one or more further optional elements X from the group Mo, Pd, Ni, Ti, V, W, and B are present in the alloy, the total amount of elements X is preferably up to 7 at.%, more preferably up to 3 at.%.

[0020] Preferably, if a further element X from the group Mo, Pd, Ni, Ti, V, W and B is present in the alloy, it is only one of these elements.

[0021] Preferably, in the sputtering targets of the present invention, Co is present in the CoZrTa(X) alloy in an amount of at least 75 at.%, more preferably at least 90 at.%.

[0022] Said CoZrTa(X) alloys consist of Zr, Ta, optionally one or more further elements X from the group of Mo, Pd, Ni, Ti, V, W, and B, and Co, i.e. Co constitutes the remainder of the atoms in the alloy.

[0023] The sputtering target of the present invention has a maximum magnetic permeability μ max is preferably 50 or less, more preferably 40 or less.

[0024] Maximum permeability μ max is usually 10 or 20 or more.

[0025] More preferably, the sputtering target of the present invention has a saturation magnetization Js of 0.8 T or less, measured as Js=J(H=60 kA / m).

[0026] The saturation magnetization Js is usually 0.5 T or more.

[0027] Preferably, the magnetic leakage flux density (PTF) of the target measured according to ASTM F2086-01 at the center of a test specimen having a thickness of 8 mm is 20% or more, more preferably 25% or more.

[0028] The present invention further relates to a method for producing a sputtering target material consisting of an alloy consisting of Co, Zr, Ta and optionally one further element X from the group of Mo, Pd, Ni, Ti, V, W, and B, which method comprises heating the alloy to a temperature of at least 700°C, more preferably at least 750°C, even more preferably at least 800°C.

[0029] Heating is preferably carried out at a temperature of up to 1000°C, more preferably up to 900°C.

[0030] Heating is typically accomplished by introducing the alloy into an oven that has been preheated to the desired temperature.

[0031] The time for heating the alloy to the above temperature is preferably 10 to 60 hours, more preferably 12 to 48 hours.

[0032] Furthermore, the present invention relates to a magnetron sputtering process in which the sputtering target of any one of the embodiments described herein is used, and to the use of the sputtering target of any one of the embodiments described herein for magnetron sputtering.

[0033] The invention is further explained on the basis of the following examples with reference to the figures. [Brief description of the drawings]

[0034] [Figure 1] 4 is a magnetic hysteresis curve of a CoZrTa alloy not according to the present invention. [Diagram 2] 1 is a magnetic hysteresis curve of a CoZrTa alloy according to the present invention.

[0035] Definition / Measurement method a) Measurement of magnetic properties The leakage magnetic flux density (PTF) was measured at the center of a test specimen with size 653 × 133 mm and thickness 8 mm according to method 2 of ASTM F2086-01.

[0036] To determine the variation of leakage flux density on the target of the present invention, PTF was measured according to method 2 of ASTM F2086-01 by placing a 4 mm thick finished machined target plate, measuring 650 x 130 mm and 4 mm ± 0.1 mm thick, on the PTF measurement stage. Measurements were taken at seven different positions equally spaced along the length of the target. Thus, all measurements were taken from the center position (65 mm) along the width (130 mm) of the target, from the left end (0 mm) along the length (650 mm) of the target. Point 1: 50mm Point 2: 142mm Point 3: 234mm Point 4: 325mm Point 5: 415mm Point 6: 508mm Point 7: 600mm

[0037] Magnetization curves were measured to compare the as-rolled and heat-treated materials using a Remagraph C from Magnet-Physik according to DIN EN 60404-4. EXAMPLES

[0038] Example 1: A CoZrTa alloy containing 91.5 at.% Co, 4 at.% Zr, and 4.5 at.% Ta was produced by conventional vacuum induction melting and casting, followed by hot rolling at 1200 °C to obtain a plate with dimensions of 653 × 133 × 8 mm.

[0039] The plates were then heat treated at 860°C for 26 hours and then air cooled, which resulted in a significant increase in the leakage flux density (PTF): the PTF before heat treatment was 10.7%, while the PTF after heat treatment was 30.2%.

[0040] As can be seen in Figure 1, the untreated material exhibits a maximum permeability of ~100 in a magnetic field of ~3 kA / m, with a saturation magnetization of 960 mT. As a consequence, only targets up to 4 mm thick can be ignited with a standard cathode.

[0041] In contrast, as can be seen from Figure 2, the heat treated alloy according to the invention showed a maximum permeability of ~30, which is three times lower at a significantly higher magnetic field of 15 kA / m, together with a lower saturation magnetization of 721 mT. There was no problem igniting a 6 mm target on the same cathode.

[0042] Example 2: Four CoZrTa alloy samples with compositions of 91.5 at.% Co, 4 at.% Zr, and 4.5 at.% Ta, respectively, were fabricated by conventional vacuum induction melting and casting, followed by hot rolling at 1200 °C to obtain four plates with dimensions of 653 × 133 × 8 mm.

[0043] The plates were then heat treated at 860° C. for 26 hours and then air cooled.

[0044] The PTF of the plate after heat treatment was 30.2%.

[0045] Measurement of the magnetization curve of the plate revealed a maximum permeability of ~30 and a saturation magnetization of 721 mT in a magnetic field of 15 kA / m.

[0046] Targets A, B, C and D with dimensions 650 × 130 × 4 mm were machined from four CoZrTa alloy plates.

[0047] The results of PTF measurements at various positions on the target are shown in Table 1.

[0048] [Table 1]

[0049] As can be seen from Table 1, (F Max -F min) / F Average The targets tested showed low variability in PTF across targets, as represented by low values ​​of . The initial disclosure of this specification includes at least the following aspects. [1] A sputtering target made of an alloy consisting of Co, Zr, Ta, and optionally one or more further elements X from the group of Mo, Pd, Ni, Ti, V, W and B, wherein the maximum magnetic permeability μ max and / or a maximum pass through flux (PTF) variation (F Max -F Min ) / F Average is 0.2 or less, preferably 0.15 or less, and most preferably 0.10 or less. [2] The sputtering target according to [1], wherein Ta is present in the alloy in an amount of 2 to 8 at. %. [3] The sputtering target according to [1] or [2], wherein Zr is present in an amount of 2 to 8 at. %. [4] The sputtering target according to any one of [1] to [3], wherein one or more further elements X from the group consisting of Mo, Pd, Ni, Ti, V, W and B are present in the alloy in a total amount of up to 7 at.%. [5] The maximum magnetic permeability μ of the target max The sputtering target according to any one of [1] to [4], wherein the Mn content is 50 or less, and preferably 40 or less. [6] The sputtering target according to any one of [1] to [5], wherein the target has a magnetic pass through flux (PTF) of 20% or more, measured in accordance with ASTM F2086-01 at the center of a test piece having a thickness of 8 mm. [7] A method for producing a sputtering target consisting of an alloy consisting of Co, Zr, Ta and optionally one or more further elements X from the group of Mo, Pd, Ni, Ti, V, W and B, characterized in that the method comprises heating the alloy to a temperature in the range of 700-1000°C, preferably 800-900°C. [8] The method according to [7], wherein the alloy is heated for 10 to 60 hours, preferably 12 to 48 hours. [9] A magnetron sputtering process using a sputtering target according to any one of [1] to [6], or a sputtering target manufactured according to [7] or [8].

[10] Use of a sputtering target according to any one of [1] to [6] or produced according to [7] or [8] for magnetron sputtering. Further preferred aspects of the present invention include the following. [1] A sputtering target made of an alloy consisting of Co, Zr, Ta, and optionally one or more further elements X from the group consisting of Mo, Pd, Ni, Ti, V, W and B, wherein the maximum pass through flux (PTF) fluctuation (F Max -F Min ) / F Average is 0.2 or less, preferably 0.15 or less, and most preferably 0.10 or less. [2] The sputtering target according to [1], wherein Ta is present in the alloy in an amount of 2 to 8 at. %. [3] The sputtering target according to [1] or [2], wherein Zr is present in an amount of 2 to 8 at. %. [4] The sputtering target according to any one of [1] to [3], wherein one or more further elements X from the group Mo, Pd, Ni, Ti, V, W and B are present in the alloy in a total amount of up to 7 at.%. [5] The maximum magnetic permeability μ of the target maxThe sputtering target according to any one of [1] to [4], wherein the average molecular weight is 60 or less, preferably 50 or less, and more preferably 40 or less. [6] The sputtering target according to any one of [1] to [5], wherein the magnetic leakage flux density (PTF) of the target is 20% or more, as measured in accordance with ASTM F2086-01 at the center of a test piece having a thickness of 8 mm. [7] A method for producing a sputtering target consisting of an alloy consisting of Co, Zr, Ta, and optionally one or more further elements X from the group of Mo, Pd, Ni, Ti, V, W and B, characterized in that the method comprises heat treating the formed alloy at a temperature in the range of 700-1000 ° C, preferably 800-900 ° C, for 10-60 hours, preferably 12-48 hours. [8] A magnetron sputtering process using the sputtering target according to any one of [1] to [6] or the sputtering target produced according to the method according to [7]. [9] Use of the sputtering target according to any one of [1] to [6] or the sputtering target produced according to the method according to [7] for magnetron sputtering.

Claims

1. A sputtering target consisting of an alloy consisting of Co, Zr, Ta, and optionally one or more further elements X from the group Mo, Pd, Ni, Ti, V, W and B, wherein the maximum magnetic permeability μ max and / or a maximum pass through flux (PTF) variation (F Max -F Min ) / F Average is 0.2 or less, preferably 0.15 or less, and most preferably 0.10 or less.

2. 2. The sputtering target of claim 1, wherein Ta is present in the alloy in an amount of 2 to 8 at. %.

3. 3. The sputtering target of claim 1, wherein Zr is present in an amount of 2 to 8 at. %.

4. 4. The sputtering target according to claim 1, wherein one or more further elements X from the group Mo, Pd, Ni, Ti, V, W and B are present in the alloy in a total amount of up to 7 at. %.

5. The target has a maximum magnetic permeability μ of 50, preferably 40 or less. max The sputtering target according to any one of claims 1 to 4, comprising:

6. 6. The sputtering target of claim 1, wherein the target has a magnetic pass through flux (PTF) of 20% or greater, measured according to ASTM F2086-01 at the center of a test piece having a thickness of 8 mm.

7. 1. A method for producing a sputtering target consisting of an alloy consisting of Co, Zr, Ta and optionally one or more further elements X from the group of Mo, Pd, Ni, Ti, V, W and B, characterized in that said method comprises heating the alloy to a temperature in the range of 700-1000°C, preferably 800-900°C.

8. The method according to claim 7, wherein the alloy is heated for a period of from 10 to 60 hours, preferably from 12 to 48 hours.

9. A magnetron sputtering process using a sputtering target according to any one of claims 1 to 6 or a sputtering target produced according to claim 7 or 8.

10. Use of a sputtering target according to any one of claims 1 to 6 or produced according to claim 7 or 8 for magnetron sputtering.

Citation Information

Patent Citations

  • METHOD FOR MANUFACTURING SPUTTERING TARGET MATERIAL OF Co-Cr BASED ALLOY

    JP2010189751A

  • Cobalt-iron alloy sputtering target material having high magnetic field transmittance

    JP2010280964A

  • Method for producing sputtering target material

    JP2011214039A

  • Cobalt-iron alloy sputtering target with high pass through flux and method for manufacturing the same

    US20100300876A1

  • Platinum-cobalt alloy sputtering target and method for manufacturing same

    EP0535314A1